Towards a TPACK-fostering ICT instructional process for teachers: Lessons from the implementation of interactive whiteboard instruction - Koh, Joyce Hwee Ling; Divaharan, Shanti (Australasian Journal of Educational Technology, 2013)
This paper describes an on-going design-based research project that aims to develop an instructional process to facilitate pre-service teachers' technological pedagogical content knowledge (TPACK) development as they learn to integrate information and communication technology (ICT) in their teaching content subjects. In conjunction with an initiative to prepare pre-service teachers for integrating interactive whiteboard (IWB) in their teaching subjects, an instructional process comprising of tutor modelling, hands-on exploration, and group-based design was implemented. The data collected during this first implementation cycle (Cycle 1) was used to enhance the second implementation cycle (Cycle 2) through the inclusion of classroom-based case studies, subject-based design ideas and opportunities for peer sharing. The findings from both implementation cycles reveal that strategies such as tutor modelling and hands-on exploration of ICT tools appeared to be more advantageous for fostering technological knowledge and technological pedagogical knowledge. Group-based design experiences supported the pre-service teachers to formulate TPACK. The paper concludes with a discussion about the future developments of these TPACK-fostering ICT instructional processes.